Improving Functional Properties of Cassava Starch-Based Films by Incorporating Xanthan, Gellan, or Pullulan Gums. (13th January 2019) - Sapper, Mayra; Talens, Pau; Chiralt, Amparo
Abstract : The effect of the partial substitution of cassava starch in edible films for 10 and 20 wt% of gellan, xanthan, or pullulan gums was analysed in films obtained by casting. The tensile properties, barrier capacity to water vapour, and oxygen and water sorption isotherms of the samples were analysed. The blend of starch with gellan gum was effective to reduce the moisture sorption capacity of starch films while reducing water vapour permeability, enhancing the film strength and resistance to break and preserving films against starch retrogradation throughout the storage time. Xanthan gum improved the tensile behaviour of the starch films, but did not reduce their water sorption capacity and water vapour permeability. Pullulan did not notably improve the functional properties of the starch films. Gellan gum at 10 and 20 wt% in the blend could be used to obtain starch films with more adequate properties for food packaging purposes.